Bangladesh : Seizing the Opportunity - World Bank Group (World Bank, Washington, DC, 2019)
These Policy Notes seek to distill key findings from a broad range of World Bank Group engagements in Bangladesh, including policy dialogue, analytical work, strategic documents, project lending and trust funded activities. They build on discussions with government counterparts, development partners, non-governmental organizations, representatives of the private sector, and other stakeholders. These Policy Notes are selective in their coverage, and include synopses on each topic, highlighting key issues and challenges, and concluding with actionable policy recommendations. They cover a broad range of policy issues but are not intended to be comprehensive or exhaustive. This effort seeks to make these findings readily available to the incoming government of Bangladesh and support them in achieving their national objectives. The Policy Notes start with an overview section which brings together the key issues and is followed by sector-specific notes which have been compiled under four broad thematic groupings.